2006
DOI: 10.1364/oe.14.006178
|View full text |Cite
|
Sign up to set email alerts
|

In vivo optical biopsy of hamster oral cavity with epi-third-harmonic-generation microscopy

Abstract: The first in vivo optical virtual biopsy based on epi-third-harmonic-generation (THG) microscopy is successfully demonstrated using Syrian hamster oral mucosa as a model system. Without complex physical biopsy procedures, epi-THG microscopy can provide high spatial resolution dynamic images of oral mucosa and sub-mucosa in all three dimensions. The demonstrated intra-vital epi-THG microscopy provide high resolution observation of blood flow in the capillary and could be a promising tool to image angiogenesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 33 publications
(16 reference statements)
3
44
0
Order By: Relevance
“…Exogenous application of acetic acid, which reversibly crosslinks nucleoproteins, can further enhance THG contrast in intact nuclei by changing their refractive index . This can be exploited to improve the detection of ( pre-)cancerous lesions in mucosal tissues with optical biopsies, based on the presence of abnormalities in nuclear morphology and nucleocytoplasmic ratios that are typical for malignant cells Tai et al, 2006;Tsai et al, 2011).…”
Section: Box 1 Label-free Imaging Modalities In Life Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous application of acetic acid, which reversibly crosslinks nucleoproteins, can further enhance THG contrast in intact nuclei by changing their refractive index . This can be exploited to improve the detection of ( pre-)cancerous lesions in mucosal tissues with optical biopsies, based on the presence of abnormalities in nuclear morphology and nucleocytoplasmic ratios that are typical for malignant cells Tai et al, 2006;Tsai et al, 2011).…”
Section: Box 1 Label-free Imaging Modalities In Life Sciencesmentioning
confidence: 99%
“…THG has the potential to complement these existing imaging approaches. The applicability of THG in optical biopsies has been demonstrated in hamster and human oral mucosa, as well as human skin and adipose tissue (Chen et al, 2009;Tai et al, 2005Tai et al, , 2006Tsai et al, 2011Tsai et al, , 2013. Furthermore, the image contrast generated using THG is suitable for discriminating melanoma and basal cell carcinoma lesions from normal skin and benign nevi .…”
Section: Virtual Optical Biopsymentioning
confidence: 99%
“…Harmonic generation microscopy (HGM) has emerged as an important imaging modality in biological study, [1][2][3][4][5][6][7][8][9] especially in in vivo applications [10][11][12][13][14][15][16][17] because of its nonlinear and noninvasive nature. Our preliminary in vivo clinical studies indicated that HGM can provide a sub-micron spatial resolution, low photodamage and phototoxicity, reduced dye toxicity as a result of the minimized use of external fluorophores, and low photobleaching.…”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary in vivo clinical studies indicated that HGM can provide a sub-micron spatial resolution, low photodamage and phototoxicity, reduced dye toxicity as a result of the minimized use of external fluorophores, and low photobleaching. In human skin, third-harmonic generation (THG) microscopy can provide intrinsic contrasts in elastic fibers, 17 cytoplasmic membrane, 13 nucleus, 13 actin filaments, 18 lipid bodies, 19 hemoglobin, 20 and melanin. 21 With the combination of THG and second-harmonic generation (SHG) processes, multi-harmonic generation microscopy (HGM) is an ideal imaging tool for morphological visualizations of human skin.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an interface in either refractive index and/or χ (3) is required for significant THG [12,13]. This property of THG is used in label free imaging in both biology and the material sciences [14][15][16][17][18]. Due to the nonlinear nature of the interaction, THG has inherent optical sectioning properties and thus true three-dimensional imaging capability.…”
Section: Introductionmentioning
confidence: 99%